(untitled) (Indian Journal of Public Health Research & Development, 2021)
Background: A number of alternatives has been proposed, including umbilical cord blood transplant (UCBT), in patients who do not matched donors for hematopoietic stem cell transplantation (HSCT). However, there are conflicting results regarding the role of the two units UCBT (dUCBT) compared to single unit (sUCBT). The present systematic review and meta-analysis aimed to compare the outcomes of dUCBT versus sUCBT in patients without suitable HLA-matched donor Material and Methods: We performed an electronic search in the following bibliographic databases: Medline via PubMed, SCOPUS, Web of Science, and Cochrane Central Register of Controlled Trials (CENTRAL). Both prospective and retrospective studies which compared sUBCT and dUBCT were included. Data were analysed using RevMan version 5.3 for windows. Results: The present review included 12eligible studies. The overall effect estimates did not favour either of the two groups in terms of neutrophil engraftment (OR =0.92, 95% CI [0.71, 1.19]; p =0.52), palatals engraftment (OR = 1.10, 95% CI [0.79, 1.53]; p =0.59), relapse rates (OR = 1.31, 95% CI [0.82, 2.09]; p =0.26) 5-year disease-free survival (OR = 0.87, 95% CI [0.59, 1.28]; p =0.49), and 5-year overall survival (OR Figure.6). However, the overall effect estimates favoured sUCBT group over the dUCBT group in term of the incidence of grade 2-4 GVHD (OR = 0.66, 95% CI [0.45, 0.97]; p =0.03). Conclusion: In conclusion both sUCBT and dUCBT have comparable results in terms of engraftment success, relapse rates, transplant-related mortality, and overall survival. However, dUCBT is associated with higher risk of acute GVHD which further limit any potential advantages of the dUCBT.